Dramatically enhanced thermoelectric performance of MoS2 by introducing MoO2 nanoinclusions. Issue 5 (9th January 2017) - Kong, Shuang; Wu, Tianmin; Yuan, Min; Huang, Zhiwei; Meng, Qing-Long; Jiang, Qike; Zhuang, Wei; Jiang, Peng; Bao, Xinhe
Abstract : Adopting an oxygen doping strategy, the thermoelectric efficiency of MoS2 can be enhanced up to 50 times with the best performance appearing along the cross-plane direction. Abstract : Two-dimensional transition-metal dichalcogenide semiconductors (TMDCs) with layered structures, such as MoS2, hold great potential to become economic and nontoxic thermoelectric materials. Application of TMDCs is hampered, however, by their insignificant power factors which cancel the advantage of their intrinsically low thermal conductivities along the cross-plane direction and lead to less satisfactory overall thermoelectric performances. Here we report that, by adopting an oxygen doping strategy, the thermoelectric efficiency of MoS2 can be enhanced up to 50 times with the best performance appearing along the cross-plane direction. Our further characterization suggests that this plausible improvement originates from the MoO2 nanoinclusions, which enhance the electrical conductivity and Seebeck coefficient, while suppressing the thermal conductivity at the same time. The unexpected simultaneous enhancement of the electrical conductivity and Seebeck coefficient after doping is explained using an electron relaxation time model. We therefore provide a general strategy towards improving the thermoelectric performance of TMDCs.